Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (bioRxiv (Cold Spring Harbor Laboratory), 2025)
Abstract Reproduction is often more thermally sensitive than survival. Thus, understanding the thermal sensitivity of reproductive interactions is crucial given global warming. However, it is unknown how temperature influences female control over fertilization after mating ( i.e., cryptic female choice). We tested how temperatures relevant to current conditions and climate change projections influence cryptic female choice in a marine fish, Symphodus ocellatus . Under typical conditions, females bias fertilization dynamics to favor dominant males. We find that warmer temperatures decrease female influence on sperm velocity and reduce the expected paternity of dominant males. Our results demonstrate that temperatures relevant to climate change can shift the balance between mate choice and male-male competition. Thus, climate change may influence sexual selection, leading to evolutionary changes in reproductive traits.
Keywords: Geology; Oceanography; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Zenodo (CERN European Organization for Nuclear Research), 2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy